Kebijakan Pemerintah Indonesia dan Thailand dalam Penanggulangan HIV AIDS - Kurniawan, Fajar; Lisnawati; Tawakkal; Nurmala, Ira; Nasus, Evodius (Journal of International Multidisciplinary Research, 2023)
Introduction:  WHO's global health sector strategy 2022–2030 on HIV goals to reduce HIV infections from 1.5 million by 2020 to 335,000 by 2030, and deaths from 680,000 in 2020 to below 240,000 by 2030. The Southeast Asia Regional Action Plan (RAP) for HIV (2017–2021) provides a clear vision of "zero new infections, zero HIV-related deaths, and zero discrimination" and a goal to "End the AIDS epidemic as a health threat by 2030".  Methods: Qualitative research by understanding the phenomenon of what the research subjects experienced, In this study, the authors used a descriptive method, which aims to describe the facts of the Indonesian government's policy and the Thai government's policy in tackling HIV AIDS cases in each country. Results: People diagnosed with HIV should be offered and associated with antiretroviral treatment (ART) as soon as possible after diagnosis and monitored periodically using clinical and laboratory parameters, including tests to measure the virus in the blood (viral load). Indonesia's policies in dealing with HIV AIDS are: Government Policy, Treatment, treatment and support for PLHIV, Conducive Environment, Sustainability of Countermeasures. Meanwhile, Thailand's state policy is: Prevention, Treatment and treatment, Cooperation in countermeasures and creating a conducive environment for PLHIV. Conclusion: It is known that in principle, the prevention and treatment of HIV AIDS refers to the world health organization and is developed based on the needs of each local government by looking at several ethnicities, races and religions as strategies in accelerating their prevention